Respuestas
Respuesta dada por:
2
Respuesta:
2
Explicación paso a paso:
A=4-4+1+1
A=2
de nadaaa
Respuesta dada por:
1
Respuesta:
-6
Explicación paso a paso:
A =
-
+
+ ![\sqrt[3]{27} ^{0} \sqrt[3]{27} ^{0}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B27%7D+%5E%7B0%7D)
A = -4 - 4 + 1 + ![\sqrt[3]{1} \sqrt[3]{1}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B1%7D)
A = -4 - 4 + 1 + 1
A = -8 + 1 + 1
A = -7 + 1
A = -6
Mi comentario:
Espero que te haya ayuda :3
Preguntas similares
hace 2 años
hace 5 años
hace 5 años
hace 5 años
hace 7 años
hace 7 años